FAKTOR – FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA DALAM MEMILIH MATA KULIAH PAKET KRIYA ANYAM PROGRAM STUDI PENDIDIKAN SENI RUPA DI JURUSAN SENI RUPA FBS UNP PADANG - Arif Habibi, Eswendi, Ernis (Universitas Negeri Padang, 2013)
The purpose of this research is to get information and to describe about: the factors which effect to interest of students in choise Mata Kuliah Paket Kriya Anyam Program Studi Pendidikan Seni Rupa in Jurusan Seni Rupa FBS UNP Padang. The subject of research is the students of Program Studi Pendidikan Seni Rupa FBS UNP Padang. While the kind of research is quantitative wiht use descriptive metodh for disriptive or know the factor inner urge, the factor of social motif, factor emosional which effect interest student on the choice mata kuliah paket Kriya Anyam. The source in this research is primary data which is taken directly from the respondent trough questionnaire. To technic analyze the data uses descriptive, analysis with descriptive percent of frekuency and mean by using SPSS version 16,00 Program. The findings of the study showed that the factor inner urge is the good factor with percent 47,73 %. The factor of social motif is the good factor with percent 50 %. factor emosional is the good factor with percent 47,7 % effect interest student on the choice mata kuliah paket Kriya Anyam.